2022
DOI: 10.15275/rusomj.2022.0313
|View full text |Cite
|
Sign up to set email alerts
|

Role Of Retroelements In The Development Of COVID-19 Neurological Consequences

Abstract: Retroelements play a key role in brain functioning in humans and other animals, since they represent dynamic regulatory elements controlling the expression of specific neuron types. The activity of retroelements in the brain is impaired under the influence of SARS-CoV-2, penetrating the blood-brain barrier. We propose a new concept, according to which the neurological complications of COVID-19 and their long-term effects are caused by modified expression of retroelements in neurons due to viral effect. This ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…The TMPRSS2 gene, which is responsible for SARS-CoV-2 penetration into the cell [ 3 ], has been repeatedly implicated in COVID-19-related outcomes [ 10 , 24 , 32 ]. Nevertheless, in the present study we observed a combined effect of TMPRSS2 rs4290734 with NR1H2 rs1405655 on accompanying neurological complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TMPRSS2 gene, which is responsible for SARS-CoV-2 penetration into the cell [ 3 ], has been repeatedly implicated in COVID-19-related outcomes [ 10 , 24 , 32 ]. Nevertheless, in the present study we observed a combined effect of TMPRSS2 rs4290734 with NR1H2 rs1405655 on accompanying neurological complications.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the SARS-CoV-2 virus on the respiratory system, cardiovascular system, and gastrointestinal tract has been repeatedly demonstrated [ 1 , 2 ]. Together with epidemiological data on disease severity related to anthropometric parameters and concomitant chronic pathology [ 1 ], the role of genetic factors in COVID-19 illness and disease severity has been reported (for review, see [ 2 , 3 , 4 ]). Twin studies have elucidated a substantial genetic influence for predicted COVID-19, with a concordance rate of 80% in MZ twins [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation